The use of the vibroacoustic system for determining the range of a ski jump for training athletes - Kiesewetter, D.; Malyugin, V.; Korotkov, K.; Zyryanov, S. (17th Annual Convention and International Conference of the International Network of Sport and Health Science, 27-29 May 2021, St. Petersburg, Russia, 2021)
INTRODUCTION: The vibroacoustic system for determining the distance of a ski jump can be either additional to the existing video systems, or an alternative. The fully automated system allows coaches to receive data on the acceleration speed and jump range in real time during the training process, create a database of results, plan the training process, pay attention directly to the athlete`s training process, and thereby improve the quality of training of jumpers METHODS: The system uses accelerometers or fiber-optic vibration sensors, analog-to-digital converters, data collection system, network computer equipment and external display devices- display boards. The system is equipped with a remote start control, which allows coaches to ensure the safety of the training process of athletes when performing ski jumps. It is possible to transfer data to the trainer`s tablet computer.